Performance Analysis of Capacity and Parking Room Needs for Basement the Badung Market - Sutapa, Ketut (International Journal of Psychosocial Rehabilitation, 2020)
Badung Market is one of the largest markets in the city of Denpasar, has motorcycle parking in the basement. The purpose of this study was to analyze the performance of motorcycle parking in the basement section. From the analysis it was found: the highest parking volume during 6 hours of observation was for motorbikes of 917 vehicles that occurred on Friday 29 June 2019, the average duration of parking was 1.07 hours/vehicle. Parking changes for each vehicle is 3 vehicles/parking lot. The highest accumulation of 368 vehicles occurred from 09.45 - 10:00 am. Parking capacity of 357 vehicles. The parking space capacity needed is 164 SRP / hour. Parking supply of 1,923 vehicles. Parking index of 84.77% <100%, means in safe conditions. The need for parking spaces is 82 parking lots.